Augmented Reality to Interior Design Company Performance - Septiyanti, Septiyanti (Swiss German University, 2019)
Interior design is an industrial company that works of flow from visual drawing into implementation construction of interior design drawing on site as a framework to fulfilled demand of client needed. Each day interior design company market becomes more high competitiveness as a national or even as a global market, and demand to fulfill with adequately performance to reach global market. In this report depart from previous comprehension; augmented reality can be a purpose effort interior design application for environment experience from computing interaction.